1997
DOI: 10.1017/s0950268896007212
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of Escherichia coli O157 in fourteen cattle herds

Abstract: Escherichia coli O157 shedding in 14 cattle herds was determined by faecal culture at intervals of approximately 1 month for up to 13 months. The overall prevalence was 1.0% (113/10832 faecal samples) and 9 of the 14 herds were detected as positive. Herds positive 2 years previously (n = 5) had a higher prevalence of positive cattle (median = 1.9%) than herds which had been negative on a previous sampling (n = 8, median = 0.2%). Weaned heifers had a higher prevalence (1.8%) than did unweaned calves (0.9%) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
212
6
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(247 citation statements)
references
References 13 publications
23
212
6
2
Order By: Relevance
“…The prevalence of EHEC O157 in cattle has been reported to be 0.2-60.4% in the United States [10,13,23,28], 1.9% in Australia [7], and 4.2-66.7% in Europe [5,6,16,24]. In Japan, it was reported that the isolation rate of the EHEC was between 0.3% [12] and 6.5% [15] in faeces samples from animals delivered to a slaughterhouse.…”
Section: Shiga Toxin (Stx)-producing Escherichia Coli (Stec) Ismentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of EHEC O157 in cattle has been reported to be 0.2-60.4% in the United States [10,13,23,28], 1.9% in Australia [7], and 4.2-66.7% in Europe [5,6,16,24]. In Japan, it was reported that the isolation rate of the EHEC was between 0.3% [12] and 6.5% [15] in faeces samples from animals delivered to a slaughterhouse.…”
Section: Shiga Toxin (Stx)-producing Escherichia Coli (Stec) Ismentioning
confidence: 99%
“…EHEC O157 was also isolated from environmental samples, though the isolation rate was low in comparison with that from faeces. Porter et al [21] and Cobbold et al [10] reported that EHEC O157 was more usually isolated from samples from slurry or in close proximity to the milking parlour. In this study, it was notable that EHEC O157 was detected not only in bedding and the feed trough being in direct contact with the cattle, but from the barn alley as well.…”
Section: Isolation and Prevalence Of Ehec O157 From Faeces Of Heifersmentioning
confidence: 99%
“…EHEC O157 can be isolated from various animals such as cattle [2,4,5,8,9,12,16,23], sheep [6], deer [1], and so on. In particular, it is often isolated from faeces of cattle showing no clinical signs of disease.…”
mentioning
confidence: 99%
“…In particular, it is often isolated from faeces of cattle showing no clinical signs of disease. It was reported that the prevalence of EHEC O157 in cattle was 0.2-28% in the United States [7,8,23], 1.9% in Australia [5], and 4.2-20% in Europe [2,4,9,16]. Therefore, cattle can harbour the organisms in their faeces and are regarded as a natural reservoir and source of infection [3].…”
mentioning
confidence: 99%
“…E. coli O157:H7 has been implicated in outbreaks from a variety of foods including raw milk, undercooked ground beef, fermented meat, and lettuce (Ackers et al, 1998;Armstrong, Hollingsworth, & Morris, 1996;Hancock, Besser, Rice, Herriott, & Tarr, 1997;Mao, Doyle, & Chen, 2001). Milk contamination occurs usually during milking, although it is possible during storage and transportation.…”
Section: Introductionmentioning
confidence: 99%